Sleep Deprivation and Cognitive Performance: The Effects Of Varying Levels Of Sleep Deprivation On Cognitive Tasks - Riya Gupta; Rajat Kanti Mitra (International Journal of Trends in Humanities, 2025)
The present study investigates the relationship between sleep deprivation and cognitive performance across various cognitive domains, with a focus on gender differences. A total of 139 participants were assessed using the Pittsburgh Sleep Quality Index (PSQI) and the Cognitive Failures Questionnaire (CFQ). The results revealed a moderate positive correlation between poor sleep quality and cognitive failures (r = 0.50, p < .001), indicating that individuals with greater sleep disturbances experienced more frequent cognitive lapses. Significant gender differences were observed, with female participants reporting higher PSQI and CFQ scores compared to males. These findings highlight the critical impact of sleep quality on cognitive functioning and emphasize the need for targeted sleep hygiene interventions, particularly for women. The study contributes to the understanding of how varying degrees of sleep deprivation affect cognitive processes and underscores the importance of addressing sleep-related issues to enhance mental efficiency and everyday functioning
Keywords: CFQ; PSQI; Sleep Deprivation; cognitive failures; cognitive performance; gender differences